2007
DOI: 10.1038/modpathol.3800711
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of NDRG1 is an indicator of poor prognosis in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma is a highly lethal cancer that typically has poor prognosis. Prognostic markers can help in its clinical management and in understanding the biology of poor prognosis. Through an earlier gene expression study, we identified N-Myc downregulated gene 1 (NDRG1) to be significantly highly expressed in hepatocellular carcinoma compared to nontumor liver. As NDRG1 is a differentiation-related gene with putative metastasis suppressor activity, we investigated the clinical significance of its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
84
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(95 citation statements)
references
References 37 publications
7
84
1
Order By: Relevance
“…In line with these preclinical findings NDRG1 expression is associated with a favorable prognosis in patients with breast, colon or pancreatic cancer [28,30,31], but associated with more aggressive disease in cervical or liver cancer [32,33]. In these studies, effects on tumor growth and therapy-modifying properties of NDRG1 are not separable.…”
Section: Csupporting
confidence: 66%
“…In line with these preclinical findings NDRG1 expression is associated with a favorable prognosis in patients with breast, colon or pancreatic cancer [28,30,31], but associated with more aggressive disease in cervical or liver cancer [32,33]. In these studies, effects on tumor growth and therapy-modifying properties of NDRG1 are not separable.…”
Section: Csupporting
confidence: 66%
“…The function of this protein remains unclear, and some controversy regarding its role in cancer exists. Some studies suggest NDRG1 involvement in metastatic suppression, whereas others show higher expression of this protein, likely related to metastasis (51)(52)(53)(54)(55). The difference in subcellular localization of NDRG1 may be important for its function, and we therefore remain open to the concept that it plays some role in the development of metastases.…”
Section: Discussionmentioning
confidence: 97%
“…Interleukin 1 beta regulates inflammation signal pathway 28 and accelerates the expression level of MMP and TIMP. 29 It was reported that N-myc downstream regulated 1 regulates angiogenesis in hepatocellular carcinoma, 30 and B-cell leukemia/lymphoma 2 protein promotes apoptosis. MiR-29a indirectly regulated these fibrosis-related genes resulting in the suppression of liver fibrosis in this study.…”
Section: Controlling Liver Fibrosis Through Preventionmentioning
confidence: 99%